Effect of initial temperature on joint of aluminum alloy to galvanized steel welded by MIG arc brazing-fusion welding process. Issue 9 (October 2016) - Ma, Hong; Qin, Guoliang; Bai, Xiaoyang; Wang, Liyuan; Liang, Zhida
Abstract The variation of initial temperature of the base metal is conducted by a preheat treatment process, and its effect on metal insert gas (MIG) arc dissimilar metal brazing-fusion joint of aluminum alloy (Al) to steel plate is studied. Results show that though increasing the initial temperature of base metal, the joint appearance improves and wetting ability of liquid Al on steel becomes better. Three different zones are observed at brazed interface in all the joints. Zn-rich zone at weld toe and Zn-rich zone at weld root are characterized by the existence of Zn, while central zone is identified due to the formation of intermetallic compounds (IMCs) layer. The IMCs layer becomes thicker with the rise of initial temperature because of the increased peak temperature. At the initial temperature of 100 °C, the joint achieves the highest tensile strength of 180 MPa, which is equivalent to 80 % of that of Al alloy base metal and fractures at heat affected zone on Al side. The initial temperature of base metal influences the mechanical properties and fracture position of the joint through governing the thickness of IMCs layer and wetting ability of liquid Al alloy on the surface of steel.